Formation enthalpy, thermodynamic stability, lattice energy of (Er, Co)-doped Bi2O3. (January 2018) - Matskevich, N.I.; Wolf, Th.; Adelmann, P.; Fuchs, D.; Semerikova, A.; Matskevich, M.Yu.
Abstract: Solution calorimetry, using 1 mol dm −3 HCl as a solvent, has been used to study for the first time the thermochemistry of Bi2.67 Er0.33 CoO5.83 . For the first time, the standard formation enthalpy of the phase has been determined as following: Δf H o (Bi2.67 Er0.33 CoO5.83, s, 298.15 K) = −1406.9 ± 8.6 kJ mol −1 . The thermodynamic stability at room temperature has been assessed. The results show that investigated phase is thermodynamically stable with respect to decomposition to the constituent binary oxides. It is important to establish thermodynamic stability for solving problem of Bi2 O3 stabilization. It is shown that the lattice energies for Bi2.67 Er0.33 CoO5.83 calculated on the basis of Born-Haber cycle and Kapustinskii rule are in a good agreement. For the first time, we measured the magnetic characteristics of Bi2.67 Er0.33 CoO5.83 and established that the Bi2.67 Er0.33 CoO5.83 phase has paramagnetic properties.